2007
DOI: 10.1177/089686080702700215
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Initiation of CAPD following Percutaneous Catheter Placement without Break-in Procedure

Abstract: Objective To evaluate the effect of a modified method of percutaneous catheter placement without a break-in procedure on the development of catheter-related complications in patients on continuous ambulatory peritoneal dialysis (CAPD). Design A prospective, observational clinical study. Setting Peritoneal dialysis (PD) units of two university-based hospitals. Patients and Methods This study included 51 consecutive patients on CAPD. A straight double-cuffed Tenckhoff catheter with a straight intraperitoneal seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(133 citation statements)
references
References 19 publications
6
122
2
3
Order By: Relevance
“…As described previously, all PD catheters were inserted by a nephrologist with a modified percutaneous placement method using guidewire. 11 All PD catheters were doublecuffed, straight-end, Tenckhoff catheters with a swan neck (SN) or non-swan neck (NSN) configuration. PD was initiated without a break-in period immediately after catheter insertion.…”
Section: Protocol For Detecting and Correcting Catheter Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…As described previously, all PD catheters were inserted by a nephrologist with a modified percutaneous placement method using guidewire. 11 All PD catheters were doublecuffed, straight-end, Tenckhoff catheters with a swan neck (SN) or non-swan neck (NSN) configuration. PD was initiated without a break-in period immediately after catheter insertion.…”
Section: Protocol For Detecting and Correcting Catheter Migrationmentioning
confidence: 99%
“…Our previously published results have shown that most of catheter migration did not associate with catheter malfunction in these PD population. 11 Our practice is to detect catheter migration without poor outflow early and then to attempt conservative management with rigorous catharsis using high doses of oral lactulose. Unlike the results of previous studies, fluoroscopic or laparoscopic procedures and surgical revision are rarely needed to restore catheter migration in our centre.…”
mentioning
confidence: 99%
“…11 The resulting tight catheter securing improved the catheter outcome irrespective of the surgical 12,13 or percutaneous insertions. 11 In both of our insertion techniques, similar catheter securing was achieved through a combination of an intramuscular tunnel and two additional purse-string sutures. Although our study had the limitation of a retrospective design, an initial hospital stay during the break-in period, prospective data recording and the patient follow up exclusively in the PD clinics ensured an adequate capturing of the catheter-related outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…These modifications focused on a tight inner cuff fixation either by additional sutures around the inner cuff 13 or by inner cuff securing in an intramuscular tunnel. 11 Apparently, these results have a tremendous clinical relevance; however, owing to the single arm designs, these studies could not exclude a confounding effect of other known risk factors for catheter leak on the observed results.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation